A metagenome-wide association study of gut microbiota in hepatitis B virus-related cirrhosis in northwest China - Feng, Meirong; Chai, Yan; Li, Jinna; Wang, Qi; Zhang, Dekui (Frontiers in Genetics, 2025)
Background and purposeIn recent years, research on the relationship between hepatitis B virus-related cirrhosis (HBV-LC) and gut microbiota has grown, but studies focusing on the Northwest Chinese population are scarce. This study characterized the gut microbiota composition and function in HBV-LC patients vs. healthy individuals in Northwest China, aiming to provide a scientific basis for region-specific precision therapies.Materials and methodsA cross-sectional study enrolled 43 HBV-LC patients and 43 age-/sex-matched healthy controls (HC) from Gansu Province. Clinical parameters including liver function, blood routine, coagulation function, blood biochemistry were measured. Shotgun metagenomic sequencing was conducted to analyze gut microbiota taxonomic composition and function.ResultsHBV-LC patients showed significantly elevated alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), γ-glutamyl transferase (γ-GGT), prothrombin time, international normalized ratio (INR), and thrombin time, but reduced triglycerides (TG), total cholesterol (TC), erythrocytes, thrombocytes, total protein, albumin, and prothrombin time activity (PT-ratio). Alpha-diversity based on Shannon and Simpson indices was lower in HBV-LC. At the genus level, Bacteroides, Prevotella, Escherichia, Parabacteroides, Veillonella, and Klebsiella were enriched in HBV-LC, while Bifidobacterium, Faecalibacterium, Roseburia, Ruminococcus, Anaerostipes, Blautia, Eubacterium, and Fusicatenibacter were reduced. Species-level analysis identified distinct enrichment of Prevotella copri, Bacteroides vulgatus, Escherichia coli, Fusobacterium nucleatum, and Veillonella spp. in HBV-LC. Functional analysis revealed 482 metabolic pathways. HBV-LC showed enhanced lipid, amino acid, and nucleotide metabolism, menaquinol biosynthesis, and anaerobic energy metabolism, but reduced acetate/lactate production, lactose/galactose degradation, and peptidoglycan biosynthesis. Metagenome-wide association study revealed HBV-LC-enriched opportunistic species (e.g., E. coli, Veillonella spp.) correlated positively with hepatic enzymes and coagulation parameters, and negatively with TC, TG, and erythrocyte counts.ConclusionHBV-LC patients in Northwest China exhibit altered clinical indicators, gut microbial composition (reduced diversity, increased opportunistic pathogens, decreased beneficial species), and metabolic function. These findings highlight the potential of gut microbiome-targeted interventions for regional precision medicine of HBV-LC.